Assessment of the enterprise selection and development process of the Ugandan National Agricultural Advisory Service - Kyomugisha, Elizabeth (International Food Policy Research Institute, 2008)
Agriculture is the mainstay for Uganda's economy, providing both food and foreign exchange. Liberalization of the economy and expansion of the area under cultivation led to a steady growth of the agricultural sector in the 1990s of over 4 percent per year. However, Uganda's population remains largely poor. Food crop production accounts for 65 percent of the GDP, yet agriculture continues to be characterized by low productivity. Moreover, land is increasingly becoming scarce, and a population growth rate of 3.5 percent per year prevents sustainable expansion. In view of these constraints, the National Agricultural Advisory Service (NAADS) has emphasized the importance of rural enterprise promotion to develop a market-oriented agricultural sector in Uganda. NAADS supports farmers in developing profitable enterprises and meeting demands both for quality and quantity of produce to exploit agricultural market opportunities. Most Ugandan farmers are smallholders lacking capital for investment and other resources, limiting the range of economic activities in which they might engage. Consequently, how they select enterprises to invest in is critical. This brief describes the NAADS enterprise selection process and provides an assessment of that process.